Parametric Model for Photovoltaic Cells with Bypass Diodes Under Partial Shading - Feng, Z. C.; Lombardo, Stephen J. (Journal of Vibration Testing and System Dynamics, 2026)
We study the disproportional effect of non-uniformity on a system of photovoltaic cell network. When a cell is partially shaded, besides the loss from the shaded cell, the power output of the whole cell network is significantly affected. Although this effect is well known in the solar cell community, the theoretical analysis has relied on one or more approximations or specially defined functions. In this paper, we present a parametric formulation of photovoltaic cells in which the output voltage and current relationships are described by explicit functions parametrized by the voltage over the cell diode. No additional approximations or specially defined functions are required to study the output characteristics. We further show that the model remains unchanged when applied to a network of many identical PV cells either in parallel or in series; the parameters for the network can be obtained from those of the cell. Incorporating interpolation in calculation, the model can be used to study a network with dissimilar cells, specifically a network with a partially shaded cell. We show that the voltage over the shaded cell becomes negative and power is dissipated over the shaded cell. The model is also conveniently used to study the network output characteristics when bypass diodes are included in the PV network.